Analysis of Tree Fall Hazard Risk: A Case Study at the University of Mataram Campus - Suripto; Supardiono Supardiono; Rachmawati Noviana Rahayu; Lalu Muhammad Aby Dujana; Feby Ayu Genggelang (Jurnal Penelitian Pendidikan IPA, 2025)
The Mataram University campus has shade trees in almost all area units, some of which are still quite ideal and some of which show problems with tree architecture deviations, such as trunk declivity and canopy inclination, which can cause the risk of tree fall. This study was conducted to analyze the distribution of tree fall risk based on tall, trunk declivity and canopy inclination on the Mataram University campus. The sample area was taken using the purposive sampling method and then sampling trees in each sample area unit using the quarter method. Tree variables observed were tall, trunk declivity and canopy inclination. The data were processed respectively to produce tree tall, trunk declivity, and canopy inclination classes. These data were then further analysed in an integrated manner to produce a value of tree-fall hazard risk. These tree-fall hazard values were interpreted into 5 categories, namely not hazardous, somewhat hazardous, quite hazardus, hazardous, and very hazardous. The results show that of the 108 shade trees on the Mataram University campus, 38.01% of the trees were in categories requiring immediate attention or action (moderately hazardous to very hazardous). Zone 1 was the only zone with the highest risk (0.93% very hazardous).